CRIMINAL RESPONSIBILITY FOR PEDOPHILIA UNDER GENERAL, TRADITIONAL AND ISLAMIC LAWS - Fitri Wahyuni; M. Rizqi Azmi; Riana Kesuma Ayu; Herdiansyah Herdiansyah (Kanun Jurnal Ilmu Hukum, 2022)
Pedophiles often engage in sexual interactions with underage children, whether it's "homosexual pedophilia," or "heterosexual pedophilia." This paper examines the criminal culpability of pedophiles in common law, Islamic law, and customary law. Normative legal writing research uses descriptive research methods. The writing uses the Legislative Approach for statutory interpretation, the Legal Concept Analysis Approach for analytical and conceptual analysis, and the Comparative Approach for legal system comparison. This work uses secondary library research data. This research uses descriptive and qualitative data analysis. This study suggests that pedophiles are criminally liable under the legal principle of criminal liability. They are not mentally sick or disabled, which exempts them from criminal culpability under Article 44 of the Criminal Code. Social offenses like pedophilia are sensitive because they affect human dignity. In Al-Isra' 32, Allah SWT says, "And do not come near to adultery; indeed, it is a shameful act and an evil way." Islam condemns all sexual deviance and its connected activities. Al-Israa verse 32. The two varieties of pedophilia are heterosexual, which favors females, and gay, which prefers boys through anal or vaginal penetration (3). A society's culture includes customary law. Customary law is created by the community and can be identified. Law is a habitual standard established deliberately. Customary criminal law, based on social cohesiveness and communal norms, may violate legality. Customary criminal law must have prospective orientation, restorative justice, inherent criminality, and integration in law formation and enforcement